(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This paper investigates the psychological mechanisms underlying the manipulative influence of advertising on consumer purchasing behavior and sales growth. Drawing on cognitive, emotional, and behavioral psychological theories, the study examines how advertising employs persuasion strategies – including priming, emotional conditioning, social proof, scarcity framing, and anchoring – to subconsciously steer consumer decisions. The research analyzes empirical evidence from contemporary marketing studies and proposes a conceptual framework for understanding the interplay between advertising stimuli and consumer response. Findings indicate that psychologically targeted advertising significantly amplifies sales outcomes by exploiting cognitive biases and emotional vulnerabilities of the target audience.